Intermittent fasting diet : guide + cookbook - Gillaspy, Becky; Walker, Lovoni, 1965- (Indianapolis, IN : Alpha/DK Publishing, 2020)
"You don't need to obsess over calorie tracking or endure constant hunger to lose weight--fasting is a more effective and more sustainable diet, and it won't leave you feeling hungry. By shortening the window of time during which you eat food, for example only eating two meals per day within an 8-hour time period, you are well on your way to a more healthy, adaptable body. Intermittent fasting aids weight loss, and is a key therapeutic tool for a variety of hormone- and health-related concerns. Decrease insulin resistance, reduce inflammation, improve cardiovascular health, protect the brain from disease, and more. Dr. Becky Gillaspy is your fasting coach. Select a meal plan that's done all the hard work of fine-tuning your macronutrient intake. Choose from one of four plans: low-carb, keto, dairy-free, and vegetarian. " Enjoy phenomenal recipes that are high in flavor, nutrient-dense, and oh-so-satisfying. With over 50 recipes to choose from and a variety of flavors, vegetables, and proteins, there are dishes to satisfy anyone." --Amazon.com.
"A complete guide to fasting strategies with 50+ satisfying recipes and 4 flexible meal plans."--Cover.
Includes bibliographical referernces and index.
Keywords: Fasting; Diet; Nutrition; Cooking; Cookbooks